AKTUALISASI METODE EKSPERIMEN PADA SENTRA BAHAN CAIR - Siti Khomsiyah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Keagamaan Islam UNUGHA Cilacap, 2022)
The learning model in TK Ya BAKII Kesugihan uses a central learning model, one of which is the Liquid Material play center. The center model is a model where learning focuses on the child, the learning process is centered on the center of play and when the child is in a circle. The experimental method is a way to present the lesson material by showing or demonstrating a process and the results of that process to achieve the teaching objectives. With the experimental method, children can also learn about simple experiments, such as activities carried out in Ya BAKII Kindergarten during learning at the liquid material center. With the activity of painting using candles on white paper, the picture is not visible, after the picture is rubbed with colored cotton wool, suddenly the image appears visible. As well as activities to introduce children to the colors of nature and also foster children's creativity during experiments.